2018
DOI: 10.3390/w10040475
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Uncertainty Estimation in Water Demand Forecasting Using the Model Conditional Processor

Abstract: In a previous paper, a number of potential models for short-term water demand (STWD) prediction have been analysed to find the ones with the best fit. The results obtained in Anele et al. (2017) showed that hybrid models may be considered as the accurate and appropriate forecasting models for STWD prediction. However, such best single valued forecast does not guarantee reliable and robust decisions, which can be properly obtained via model uncertainty processors (MUPs). MUPs provide an estimate of the full pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 29 publications
(70 reference statements)
0
11
0
1
Order By: Relevance
“…It is based upon the past water use, and socio-economic and climate parameters associated with the past water use. These parameters are precipitation (rain), temperature, seasonality, and evapotranspiration, water price, income, family size and other related factors [113][114][115][116]. Short-term water demand forecasting is essential for operation and management of networks whereas long-term forecasting is required by utility managers for planning and design of WDNs.…”
Section: Demand Forecast Modelsmentioning
confidence: 99%
“…It is based upon the past water use, and socio-economic and climate parameters associated with the past water use. These parameters are precipitation (rain), temperature, seasonality, and evapotranspiration, water price, income, family size and other related factors [113][114][115][116]. Short-term water demand forecasting is essential for operation and management of networks whereas long-term forecasting is required by utility managers for planning and design of WDNs.…”
Section: Demand Forecast Modelsmentioning
confidence: 99%
“…In this work, the predictive uncertainty is estimated based on a set of predictions by an autoregressive-moving average (ARMA) model and a feed-forward neural network (FFBP-NN) model [32]. The algorithm starts by selecting the training datasets that include subsets of the real observed values and subsets for the forecasted values of ARMA and FFBP-NN.…”
Section: Demand Forecastingmentioning
confidence: 99%
“…Therefore, upper and lower tail models are developed to eliminate such values. For further details, we refer the reader to [32].…”
Section: Demand Forecastingmentioning
confidence: 99%
“…The MCP technique was used by Anele et al [34] to evaluate the knowledge improvement obtained by the utilization of several predictive models and, thus, being able to estimate Predictive Uncertainty (PU) in future water demand predictions. The authors observed that MCP is suitable for water short-term predictions due to the extraction of the PU connected to the MCP forecast obtained.…”
Section: Related Workmentioning
confidence: 99%